Analisis Dan Perancangan Sistem Electronic Customer Relationship Management (E-Crm) Pada Otoxpert Jambi - Rizky Rachmadiyanto; Setiawan Assegaff; Beni Purnama (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
Otoxpert Jambi is one of the companies operating in the automotive sector with a focus on light service or quick service. Whereas in the current system, there are several issues in acquiring new customers, improving relationships with customers, and retaining customers. Based on the existing problems at Otoxpert Jambi, there is a need for a web-based Customer Relationship Management (CRM) system that can help both Otoxpert Jambi and its customers build good relationships. The purpose of this research is to analyze the service relationship between the company and customers and to design a web-based Electronic Customer Relationship Management (E-CRM) system to create a better relationship between the company and customers through features on the website. The author conducted object-oriented design, including use case diagrams, activity diagrams, class diagrams, interface design, database structure tables, and interface implementation. The result of this research is the implementation of a web-based E-CRM system that can help resolve issues, particularly those related to customer service at Otoxpert Jambi, so that the E-CRM can function effectively.